Benzodiazepine prescribing in children under 15 years of age receiving free medical care on the General Medical Services scheme in Ireland. Issue 6 (9th June 2015) - O'Sullivan, K; Reulbach, U; Boland, F; Motterlini, N; Kelly, D; Bennett, K; Fahey, T
Abstract : Objective: To examine the prevalence and secular trends in benzodiazepine (BZD) prescribing in the Irish paediatric population. In addition, we examine coprescribing of antiepileptic, antipsychotic, antidepressant and psychostimulants in children receiving BZD drugs and compare BZD prescribing in Ireland to that in other European countries. Setting: Data were obtained from the Irish General Medical Services (GMS) scheme pharmacy claims database from the Health Service Executive (HSE)—Primary Care Reimbursement Services (PCRS). Participants: Children aged 0–15 years, on the HSE-PCRS database between January 2002 and December 2011, were included. Primary and secondary outcome measures: Prescribing rates were reported over time (2002–2011) and duration (≤ or >90 days). Age (0–4, 5–11, 12–15) and gender trends were established. Rates of concomitant prescriptions for antiepileptic, antipsychotics, antidepressants and psychostimulants were reported. European prescribing data were retrieved from the literature. Results: Rates decreased from 2002 (8.56/1000 GMS population: 95% CI 8.20 to 8.92) to 2011 (5.33/1000 GMS population: 95% CI 5.10 to 5.55). Of those children currently receiving a BZD prescription, 6% were prescribed BZD for >90 days. Rates were higher for boys in the 0–4 and 5–11 age ranges, whereas for girls they were higher in the 12–15 age groups. A substantial proportion of children receiving BZD drugs are also prescribed antiepileptic (27%), antidepressant (11%), antipsychotic (5%) and psychostimulant (2%) medicines. Prescribing rates follow a similar pattern to that in other European countries. Conclusions: While BZD prescribing trends have decreased in recent years, this study shows that a significant proportion of the GMS children population are being prescribed BZD in the long term. This study highlights the need for guidelines for BZD prescribing in children in terms of clinical indication and responsibility, coprescribing, dosage and duration of treatment.